Foreign Firms and Business History in Latin America (2010)
Introduction. I. Imperialism, dependency, and business history in Latin America in the late twentieth century. II. Bringing international business concepts into history: The case of British firms and Latin American markets. Appendix: Examples of the establishment of British consumer goods manufacturing companies in Latin America, 1930-1965.